Strategi Komunikasi Korporasi PT Mayora Indah Tbk Dalam Upaya Membangun Citra Positif - Mishelia Kartika Puspitasari; Muhammad Reihan Manalu (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
This research aims to examine the corporate communication strategies implemented by PT Mayora Indah Tbk in building a positive company image. In the era of globalization and digitalization, a company's image becomes an important asset that influences consumer trust and reputation in the eyes of stakeholders. This research uses a qualitative method with a literature study approach to analyze how PT Mayora implements communication strategies to strengthen its positive image through various activities, including information transparency to investors, corporate social responsibility, and product quality management. The research results show that PT Mayora implements information transparency openly to shareholders and the public, maintains environmental sustainability, pays attention to employee welfare, and runs social programs that support the surrounding community. In addition, the company also ensures product quality through strict supervision of raw materials and the production process. All these efforts contribute to strengthening the company's positive image, which focuses on integrity, transparency, and social responsibility. This research concludes that effective corporate communication strategies can build a deep positive image, which is crucial in facing challenges and competition in today's industry.